(untitled) (Tikrit Journal of Veterinary Science, 2025)
This study evaluated the cardioprotective effects of resveratrol against isoproterenol-induced myocardial infarction in male Sprague-Dawley rats. Forty rats were randomly divided into four groups: control, resveratrol-treated, isoproterenol-treated, and a combined treatment group. Resveratrol was administered orally at 20 mg/kg/day, while isoproterenol was given intraperitoneally at 100 mg/kg. The results revealed that isoproterenol significantly increased serum levels of oxidative stress markers (MDA), inflammatory cytokine (TNF-α), triglycerides, cholesterol, and cardiac enzymes (CK-MB, cTnI, LDH), while reducing total antioxidant capacity (T-AOC) (P ≤ 0.05). esveratrol treatment significantly mitigated these alterations, restoring antioxidant levels and reducing lipid and enzyme elevations. The combination treatment group showed intermediate values, indicating a partial protective effect. In conclusion, resveratrol demonstrates promising cardioprotective properties through its antioxidant, anti-inflammatory, and lipid-lowering actions, suggesting its potential as a preventive agent against oxidative and inflammatory cardiac damage.